Sox2 acts as a rheostat of epithelial to mesenchymal transition during neural crest development - Mandalos, Nikolaos; Rhinn, Muriel; Granchi, Zoraide; Karampelas, Ioannis; Mitsiadis, Thimios; Economides, Aris N.; Dollé, Pascal; Remboutsika, Eumorphia (Frontiers in Physiology, 2014)
Precise control of self-renewal and differentiation of progenitor cells into the cranial neural crest (CNC) pool ensures proper head development, guided by signaling pathways such as BMPs, FGFs, Shh and Notch. Here, we show that murine Sox2 plays an essential role in controlling progenitor cell behavior during craniofacial development. A “Conditional by Inversion” Sox2 allele (Sox2COIN) has been employed to generate an epiblast ablation of Sox2 function (Sox2EpINV). Sox2EpINV/+(H) haploinsufficient and conditional (Sox2EpINV/mosaic) mutant embryos proceed beyond gastrulation and die around E11. These mutant embryos exhibit severe anterior malformations, with hydrocephaly and frontonasal truncations, which could be attributed to the deregulation of CNC progenitor cells during their epithelial to mesenchymal transition. This irregularity results in an exacerbated and aberrant migration of Sox10+ NCC in the branchial arches and frontonasal process of the Sox2 mutant embryos. These results suggest a novel role for Sox2 as a regulator of the epithelial to mesenchymal transitions that are important for the cell flow in the developing head.